PRODUK BIOTEKNOLOGI FARMASI BERUPA SABUN MANDI KOMBUCHA BUNGA TELANG (Clitoria ternatea L) SEBAGAI ANTIFUNGI Candida albicans - Ma’ruf, Aris; Safitri, Endang; Desmak Pertiwi, Fernanda; Ningtias, Retna Yulrosly; Trisnawati, Desi; Rezaldi, Firman; Kusumiyati, Kusumiyati; Andayaningsih, Poniyah (Jurnal Pertanian, 2022)
Telang flower kombucha besides playing an important role in the food sector as a probiotic drink, it has potential in the pharmaceutical (cosmetic) field, especially in the preparation of probiotic liquid bath soap in inhibiting the growth of Candida albicans which causes vaginal discharge in the female intimate organs. This study aims to make formulations and preparations of probiotic liquid bath soap with active ingredients from fermented kombucha telang flower solution at concentrations of 20%, 30%, and 40% in inhibiting the growth of Candida albicans. This research method is a laboratory experiment by making 4 preparations of probiotic liquid bath soap with active ingredients from fermented kombucha telang flower solution at concentrations of 20%, 30%, 40%, and soap base as a negative control and the use of biore soap available in the market as a positive control. Testing on the growth inhibition of Candida albicans using the disc diffusion method. Data analysis was carried out statistically using one-way ANOVA and further tests were carried out in the form of post hoc analysis. The conclusion in this study was that the concentration of 40% in the preparation of kombucha flower telang bath soap was the best concentration as antifungal Candida albicans with an average diameter of the resulting inhibition zone was 20.52 mm.